Enhancing international knowledge transfer through information technology: the intervention of communication culture. (1st January 2012) - Wu, Wei-Li; Lee, Yi-Chih
Nowadays, outsourcing and offshore-partnering activities have become popular business models for leading multinational enterprises. Usually, outsourcing not only helps leading multinational enterprises increase their competitive advantage, but also offers suppliers a great opportunity to learn from their international customers. Hence, it raises the issue of what factors are important for suppliers to successfully manage knowledge transfer in the international context. In the previous studies, little attention has been paid to how information technology (IT) influences cross-border knowledge transfer. In this present study, taken from the supplier's perspective, we propose that IT can improve the quality and quantity of information exchange, and have a positive influence on cross-border knowledge transfer. Based on a sample site of 206 Taiwanese suppliers and tested by the multivariate adaptive regression splines (MARS) statistical approach, the empirical results reveal that a knowledge management integrated database has a positive impact on technical knowledge transfer. Additionally, when in a low-context communication culture, video conferencing has a positive impact on technical knowledge transfer and instant messaging also has a positive impact on marketing knowledge transfer. Importantly, inter-organisational IT does not have a significant impact on knowledge transfer when in a high-context communication culture.